Social responsibility and environmental sustainability: the Case of Caixa Geral de Depósitos (Portugal) and Vale (Brazil) - Filipe, J. A. (2017)
Social responsibility requires a set of duties and obligations, whether individuals or firms in relation to society and to the communities in which the organization is operating. The tradition of social intervention in Portugal dates from the fifteenth century and the founding of Mercy. However, environmental issues have never been felt in a sensitive position in responsible business, given the weakness of industrial development which lasted until the 60’s. In Brazil, the corporate social responsibility is still particularly a big challenge, since the actions of social responsibility have not contributed effectively to improve the living conditions of society and the transformation of existing social reality. The purpose of this study is to emphasize the perspective of environmental sustainability that underpins the more general concept of social responsibility and, through the case study Caixa Geral de Depósitos, assess the strengths and weaknesses of the development of measures of social responsibility in this area in Portugal, and present the case of the company Vale, carrying out business in Brazil.